2017
DOI: 10.1038/emi.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of HIF-1α induced by influenza A (H1N1) infection is critical to the production of proinflammatory cytokines

Abstract: Infection with the influenza A (H1N1) virus is a major challenge for public health because it can cause severe morbidity and even mortality in humans. The over-secretion of inflammatory cytokines (cytokine storm) is considered to be a key contributor to the severe pneumonia caused by H1N1 infection. It has been reported that hypoxia-inducible factor 1-alpha (HIF-1α) is associated with the production of proinflammatory molecules, but whether HIF-1α participates in the acute inflammatory responses against H1N1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“…Several viruses, often associated with chronic infections, such as hepatitis C virus, herpesviruses, human papillomavirus and immunodeficiency virus (HIV), have been shown to induce HIF-1α activation, leading to metabolic cellular reprogramming and promotion of virus replication [ 31 , 34 , 35 ]. Influenza virus infection was also able to induce HIF-1α activation in lung carcinoma and monocytic cell lines; however, a lack of lung epithelial cell expression of HIF-1α in a mouse model of influenza infection was associated with enhanced virus replication [ 36 , 37 ]. HIF-1α expression and stabilization in epithelial and immune cells plays an important role in promoting inflammatory responses, as well as the production of VEGF [ 8 , 33 ], both of which are known to contribute to the pathogenesis of RSV-induced lung disease, supporting further investigation into the use of selective HIF-1a inhibitors to modulate RSV disease, keeping in mind, however, that HIF proteins are also important for repair/healing processes following acute lung injury [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several viruses, often associated with chronic infections, such as hepatitis C virus, herpesviruses, human papillomavirus and immunodeficiency virus (HIV), have been shown to induce HIF-1α activation, leading to metabolic cellular reprogramming and promotion of virus replication [ 31 , 34 , 35 ]. Influenza virus infection was also able to induce HIF-1α activation in lung carcinoma and monocytic cell lines; however, a lack of lung epithelial cell expression of HIF-1α in a mouse model of influenza infection was associated with enhanced virus replication [ 36 , 37 ]. HIF-1α expression and stabilization in epithelial and immune cells plays an important role in promoting inflammatory responses, as well as the production of VEGF [ 8 , 33 ], both of which are known to contribute to the pathogenesis of RSV-induced lung disease, supporting further investigation into the use of selective HIF-1a inhibitors to modulate RSV disease, keeping in mind, however, that HIF proteins are also important for repair/healing processes following acute lung injury [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Influenza viruses stabilize HIF-1α through impairing proteasome function and decreasing the expression of factor inhibiting HIF-1α (FIH-1) [ 38 ]. The high production of pro-inflammatory cytokines, cytokine storm, as a key contributor to severe pneumonia in patients with H1N1 infection is mediated by HIF-1α which can induce proinflammatory molecules production in the site of inflammation [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cytokine‐mediated inflammation triggered by HIF‐2α has been revealed in reflux esophagitis (Souza, Bayeh, Spechler, Tambar, & Bruick, ). An in vitro study showed that in vitro infection with influenza H1N1 virus promotes the secretion of proinflammatory cytokines by inducing nuclear translocation of HIF‐1α (Guo et al., ). HIF‐1α appears to control expression of IL‐22 in CD4 T cells (Budda, Girton, Henderson, & Zenewicz, ).…”
Section: Discussionmentioning
confidence: 99%